Integrated management for patient safety and quality of health care - Rosalba Roque González; Rosa Mayelin Guerra Bretaña; Rafael Torres Peña (Universidad de Ciencias Médicas de La Habana, 2018)
Introduction: The quality of medical services is an issue of growing concern for health professionals, researchers, the public, and governments around the world.  Commonly, in the medical care, safety has been assumed to be a separate aspect of quality, without considering that patient safety is one of the fundamental dimensions of quality. Objective: To analyze the application of integrated management based on the risks of safety and quality in the National Center for Minimal Access Surgery, using surgery of biliary lithiasis as a case study.  Material and Methods: On the basis of structure, responsibilities, and documents established for quality management, some studies of the risk factors for the safety of patients undergoing elective endoscopic surgery were carried out in three stages: preoperative, intraoperative and postoperative. Results: The risk approach changes the management of patient quality and safety from a reactive evaluation in the presence of complications and non-conformities to a proactive management of potential risks.  It has an added value of first-line personnel participation in this process that promotes the identification of potential risks, even when no failures have occurred.  Errors are learning opportunities that allow the prevention of future damage to patients. Conclusions: The integrated management for patient safety and quality with a risk-based approach guarantees excellent performance indicators in the medical care of the National Center for Minimum Access Surgery.  Keywords: quality management, patient safety, integrated management, risks of endoscopic surgery.